PI3Kγ inhibition induces immunogenic biomarkers in hematological cancer cells in vitro - Nogueira, Clara Norões (2024)
Chronic myeloid leukemia (CML) is a subtype of hematological malignancy characterized by the presence of a chromosomal translocation which results in Bcr/Abl1 gene fusion. Therapy with tyrosine kinase inhibitors revolutionized treatment of CML patients, however about 20- 30% develop resistance. The phosphoinositide 3-kinases (PI3K) are a family of lipid kinases with roles in cell signaling, activation and metabolic regulation. The PI3K pathway is found deregulated in many human cancers. Class IB PI3Kγ is enriched in myeloid cells and has important roles in innate immunology as it regulates migration, differentiation, and activation of myeloid cells. Immunogenic cell death (ICD) is a type of regulated cell death which induces immunological response against dying cancer cells, constituting an interesting therapeutic strategy. The response is activated by damage-associated molecular patterns (DAMPS), namely calreticulin (CALR), high-mobility group box 1 protein (HMGB1), heat shock proteins (HSPs), among others. As PI3Kγ displays important roles in regulating immune response in myeloid cells, the development of PI3Kγ inhibitors could be an interesting immunogenic strategy. This work aimed to assess the capability of PI3Kγ inhibitors to elicit immunogenic cell death by evaluating the presence of some of the crucial DAMPs. Expression of PI3Kγ in several cell types was detected by flow cytometry. Inhibitors used were evaluated in silico for target and pharmacological parameters prediction. Reduction of cell viability was perceived in trypan dye exclusion assay for both molecules at 3000, 1000 and 300 nM. Colony formation assay showed reduction of the number of K562 colonies at the 2000 and 1000 nM concentration for AS-605240, and at 2000, 1000 and 300 nM for IPI-145. Both inhibitors caused morphologic alterations such as shrinkage and high granularity increase. Additionally, CALR externalization was detected, while AS-605240 and IPI-145 at 1000 nM increased nuclear HMGB1. In western blot, K562 cells treated with IPI-145 reduced p62 expression, suggesting autophagic flux induction. AS-605240 at 100 nM and IPI-145 at 100, 300 and 1000 nM were able to increase phosphorylation of eIF2α. Therefore, AS-605240 and IPI-145 showed antiproliferative effects, induced cell stress and activated markers of immunogenicity. Thus, the perspective of chemotherapy associated with PI3Kγ inhibitors to elicit or burst ICD is a promising strategy, however further studies are necessary.